Divine foreknowledge, human freedom, and the burden of prophecty to contingent future events: implications for contemporary Nigeria (2018)
Questions on human freedom have been a subject of debate in the history of philosophy. Divine foreknowledge of events poses a great challenge to human freedom. Prophecy, usually, is a means of expressing God's mind on a particular person, group of people or a particular event. This paper discusses the subject of divine foreknowledge and human freedom, with a focus on the burden which prophecy creates for contingent future events. It is easy to accept that once a prophecy is made, it is final and nothing can be done again on the issue. This is in line with fatalism. This paper seeks to analyse the position that suggests that prophecy indicates inevitability of issues. This is with a view to correcting this notion because regardless of what has been revealed, humans are still responsible for their actions. This means that prophecies are somewhat open, regardless of the fact that they are divinely inspired. The study adopts the Open Theory of William Hasker on prophecy and contingent future events.